2015
DOI: 10.1038/nchem.2183
|View full text |Cite|
|
Sign up to set email alerts
|

Intermediate tunnelling–hopping regime in DNA charge transport

Abstract: Charge transport in molecular systems, including DNA, is involved in many basic chemical and biological processes, and its understanding is critical if they are to be used in electronic devices. This important phenomenon is often described as either coherent tunnelling over a short distance or incoherent hopping over a long distance. Here, we show evidence of an intermediate regime where coherent and incoherent processes coexist in double-stranded DNA. We measure charge transport in single DNA molecules bridge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
256
0
4

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 228 publications
(287 citation statements)
references
References 49 publications
27
256
0
4
Order By: Relevance
“…II. In a recent application of this technique to DNA 60 , we demonstrated that the LBP method can yield results in qualitative (and sometimes quantitative) agreement with experiments, and uncovered an intermediate coherent-incoherent transport regime 83 . An important caveat of our simulations is the fact that ballistic transport is promoted beyond what we expect in reality, since the underlying electronic structure used is static.…”
Section: Tunneling To Hopping Transition In Dnamentioning
confidence: 95%
“…II. In a recent application of this technique to DNA 60 , we demonstrated that the LBP method can yield results in qualitative (and sometimes quantitative) agreement with experiments, and uncovered an intermediate coherent-incoherent transport regime 83 . An important caveat of our simulations is the fact that ballistic transport is promoted beyond what we expect in reality, since the underlying electronic structure used is static.…”
Section: Tunneling To Hopping Transition In Dnamentioning
confidence: 95%
“…Thus, the extent of electronic delocalization among DNA bases is expected to be tunable by manipulating sequence, stacking and solvation. Recent DNA break-junction experiments of Xiang et al discovered resistance oscillations as a function of chain length, which points to a phenomenological description that involves partial coherence, but the studies do not establish the specific physical origins of the coherence and nor do they provide testable molecular designs that might be used to manipulate the coherence 9 . The present study established a molecular-resolution theory that enables the engineering of molecular assemblies that support extended coherent transport, and these principles were tested in DNA structures.…”
mentioning
confidence: 96%
“…Изучаются детали механизмов взаимодействия электронов с возмущениями цепочки нуклеотидов [23][24][25], рассчитываются вольт-амперные характеристики молекулы ДНК [26,27], анализируются способы управления характеристиками транспорта зарядов [28,29], исследуется влияние внешней среды [30], рассматриваются как перспективные сложные модификации, включающие ДНК [31][32][33][34][35][36], описываются различные прикладные возможности [37].…”
Section: Introductionunclassified